Saw It on Facebook, Drank It at the Bar! Effects of Exposure to Facebook Alcohol Ads on Alcohol-Related Behaviors. Issue 1 (2nd January 2016) - Alhabash, Saleem; McAlister, Anna R.; Kim, Wonkyung; Lou, Chen; Cunningham, Carie; Quilliam, Elizabeth Taylor; Richards, Jef I.
ABSTRACT: Using a 2 (beverage: beer versus water) × 2 (brand familiarity: familiar versus unfamiliar) × 3 (message repetition) mixed factorial experiment, this study investigated the effects of exposure to Facebook alcohol advertisements on intentions to consume alcohol and alcohol-related behaviors (gift card choice: bar versus coffee shop). Participants ( N = 121) were exposed to Facebook ads for familiar or unfamiliar beer or water brands. Participants were more likely to select a bar than a coffee shop gift card upon exposure to beer versus water ads, which was moderated by brand familiarity and risky alcohol use (Alcohol Use Disorders Identification Test [AUDIT]). In addition, participants' expression of intentions to consume alcohol was conditional to AUDIT and brand familiarity. Findings are discussed within the framework of the mere exposure and priming effects. The policy implications of social media advertising of alcohol are discussed.